تدبير الصفقات العمومية في ظل جائحة كورونا - دوباج، نادية (رضوان العنبي, 2022)
تأثر الاقتصاد المغربي بشكل كبير بتداعيات جائحة كوفيد- 19، شأنه شأن الاقتصاديات العالمية، واتخذ من أجل مواجهتها عدة إجراءات قانونية وتنظيمية بهدف التخفيف من حدتها على الفرد والمجتمع، وبما أن الصفقات العمومية تشكل الأداة التي تبرم بواسطتها مجموعة من العقود الاستثمارية، وتنفذ بمقتضاها مشاريع عمومية على أرض الواقع، فقد كان للجائحة انعكاسات على مآل الصفقات العمومية والنظام القانوني لإبرامها، على أساس أولويات الظرفية الاقتصادية والمالية. The Moroccan economy has been greatly affected by the repercussions of the Covid pandemic19Like global economies, several legal and regulatory measures have been taken in order to confront them with the aim of alleviating their severity on the individual and society, and since public deals constitute the tool by which a group of investment contracts are concluded, and public projects are implemented on the ground, the pandemic has had repercussions on the fate of Public transactions and the legal system for their conclusion, based on the priorities of the economic and financial situation.
Keywords: الاقتصاد المغربي -- التدبير الاقتصادي -- الصفقات العمومية -- جائحة كورونا "كوفيد-19"